Super-twisting SMC for MPPT and grid-connected WECS based on SCIG - Bouhenna Amina; Khodja Mohammed; Merabet Boulouiha Houari (Institute of Advanced Engineering and Science, 2021)
This paper proposes a high-order sliding mode control (HO-SMC) with the super-twisting (ST) algorithm for maximum power point tracking (MPPT) and grid-connected wind energy conversion system (WECS), based on squirrel-cage induction generator (SCIG). The main features of this control strategy are attenuation of the chattering phenomenon inherent in first-order sliding mode control and its robustness against external and internal disturbances encountered by the wind power system. The simulation is carried out under SimPowerSystems of MATLAB/Simulink to evaluate the performance and effectiveness of the proposed control compared with conventional and fuzzy logic proportional-integral (PI) controllers for three different scenarios of disturbances, a fluctuating wind speed, a grid voltage drop, and parametric variations.